Mathematical Modeling of Dual Intake Transparent Transpired Solar Collector. (21st July 2015) - Semenou, Thomas; Rousse, Daniel R.; Le Lostec, Brice; Nouanegue, Hervé F.; Paradis, Pierre-Luc
Abstract : Nowadays, in several types of commercial or institutional buildings, a significant rise of transpired solar collectors used to preheat the fresh air of the building can be observed. Nevertheless, when the air mass flow rate is low, the collector efficiency collapses and a large amount of energy remains unused. This paper presents a simple yet effective mathematical model of a transparent transpired solar collector (TTC) with dual intake in order to remove stagnation problems in the plenum and ensure a better thermal efficiency and more heat recovery. A thermal model and a pressure loss model were developed. Then, the combined model was validated with experimental data from the Solar Rating and Certification Corporation (SRCC). The results show that the collector efficiency can be up to 70% and even 80% regardless of operating conditions. The temperature gain is able to reach 20°K when the solar irradiation is high.